Treating the juvenile offender - Hoge, Robert D. (Guilford Press, 2008)
A portrait of juvenile offending in the United States / Kirk R. Williams, Louis Tuthill, and Shoon Lio -- Theoretical and research advances in understanding the causes of juvenile offending / Nancy G. Guerra... [et al.] -- Assessment in juvenile justice systems / Robert D. Hoge -- What works : best practices with juvenile offenders / Nancy G. Guerra, Tia E. Kim, & Paul Boxer -- Implementing treatment programs in community and institutional settings / Nancy G. Guerra & Caren Leaf -- How policy affects practice in the treatment of juvenile offenders : the California experience / Elizabeth Siggins & Amy Seidlitz -- Treatment of violent offenders / Paul Boxer & Paul J. Frick -- Treating gang involved offenders / Robert Nash Parker... [et al.] -- Juvenile sexual offending : an evidence-based approach to assessment and intervention / Gary O'Reilly & Clodagh Ann Dowling -- Mental health and substance abuse / Bonita M. Veysey -- Juvenile offenders with special education needs / Carolyn R. Eggleston -- The female juvenile offender / Robert D. Hoge & Lynda Robertson